2023
DOI: 10.1093/ofid/ofad172
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of COVID-19 mRNA Vaccines in Preventing COVID-19-Associated Outpatient Visits and Hospitalizations Among American Indian and Alaska Native Persons, January–November 2021: A Test-Negative Case-Control Analysis Using Surveillance Data

Abstract: Background Despite the disproportionate morbidity and mortality experienced by American Indian and Alaska Native (AI/AN) persons during the COVID-19 pandemic, few studies have reported vaccine effectiveness (VE) estimates among these communities. Methods We conducted a test-negative case-control analysis among AI/AN persons aged ≥12 years presenting for care from January 1, 2021 through November 30, 2021 to evaluate effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Many studies have already demonstrated the effectiveness of COVID-19 vaccines [13,[40][41][42]. However, this study adds to the current literature by showing that being up to…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Many studies have already demonstrated the effectiveness of COVID-19 vaccines [13,[40][41][42]. However, this study adds to the current literature by showing that being up to…”
Section: Discussionmentioning
confidence: 60%
“…Many studies have already demonstrated the effectiveness of COVID-19 vaccines [13,[40][41][42]. However, this study adds to the current literature by showing that being up to date with all eligi-ble COVID-19 vaccinations, especially booster vaccinations, can provide additional protection.…”
Section: Discussionmentioning
confidence: 66%